2014
DOI: 10.1128/iai.01951-14
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Driven Immune Cellular Maturation Is Essential for Antibody-Mediated Adaptive Immunity to Staphylococcus aureus Infection in the Eye

Abstract: bAs an immune-privileged site, the eye, and particularly the outer corneal surface, lacks resident mature immune effector cells. Physical barriers and innate mediators are the best-described effectors of immunity in the cornea. When the barriers are breached, infection can result in rapid tissue destruction, leading to loss of visual acuity and frank blindness. To determine the cellular and molecular components needed for effective adaptive immunity on the corneal surface, we investigated which immune system e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…aureus infections, also have shown a role for cellular effectors including T cells, IL-17, and IL-22. 2831 Prior studies from Taylor et al 6,7 demonstrated an important role for IL-17–producing neutrophils in host immune responses to fungal keratitis. In settings where either T-cells (RAG-1 KO mice), IL-17 activity (IL-17R KO mice), or IL-22 activity (IL-22 KO mice) was not operative, we found the MAb F598 showed no significant therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…aureus infections, also have shown a role for cellular effectors including T cells, IL-17, and IL-22. 2831 Prior studies from Taylor et al 6,7 demonstrated an important role for IL-17–producing neutrophils in host immune responses to fungal keratitis. In settings where either T-cells (RAG-1 KO mice), IL-17 activity (IL-17R KO mice), or IL-22 activity (IL-22 KO mice) was not operative, we found the MAb F598 showed no significant therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, there was a dependence on IL-17 and IL-22 in the antibody-induced protection. 55 This paper prompted many important questions. Namely, what is the impact of microbiota on neutrophil maturation and activation and where does neutrophil priming occur?…”
Section: What Is the Impact Of The Microbiome On Ocular Immunity?mentioning
confidence: 99%
“…Analysis of the mechanisms of protection mediated by Staphylococcus aureus -specific monoclonal antibody during keratitis revealed that the germ-free mice treated with the therapeutic antibody failed to mount a protective immunity against this pathogen, due to failure to recruit inflammatory cells to the site of infection. 55 The lack of protective efficacy of the monoclonal antibody in infected RAG mice or CD4 + cell–depleted mice suggested stipulation of T cell functions. Consistently, there was a dependence on IL-17 and IL-22 in the antibody-induced protection.…”
Section: What Is the Impact Of The Microbiome On Ocular Immunity?mentioning
confidence: 99%
“…Current experimental limitations are unable to resolve whether these bacteria are resident (long-term colonizers as opposed to transient, originating from the environment), metabolically active, or even alive. Although there is evidence that bacteria at the ocular surface may affect disease (de Paiva et al, 2016; Kugadas et al, 2016; Zaidi et al, 2014), this does not speak to their status as ocular surface commensals, or how they interact with the immune system to be functionally relevant to local immunity. Rather, these studies conclude that gut microbes might play a major role in disease outcome.…”
Section: Introductionmentioning
confidence: 99%